Economic Valuation of Pesanggrahan Forest in Malang Regency - Ula, Fresha Aflahul; Rohman, Fatchur; Novianti, Vivi (TROPICAL WETLAND JOURNAL, 2023)
Economic valuation is a method for revealing the importance of a forest based on monetary value. The economic valuation of the Pesanggrahan Forest is carried out to reveal the economic value of Direct Use Value, Indirect Use Value, Option Value, Existence Value, and Bequest Value to obtain the Total Economic Value (TEV) of the Pesanggrahan Forest area. The methods used to determine the economic value are Market Price, Replacement Method, and Contingent Valuation Method. The results show that Pesanggrahan Forest have a Total Economic Value IDR. 268,962,582,306. This total value is the value of the protected forest IDR. 145,753,885 and production forest IDR 123,209,166,421. This value describes the magnitude of the benefits of forest as an economic and ecological function in the Pesanggrahan Forest Area, Malang Regency. Protected forest have greater economic value than production forest, so it is hoped that forest conversion will not occur again, both in the Pesanggrahan Forest and other forest in Indonesia.